Synthesis and Characterization of Cockle Shell-Based Calcium Carbonate Aragonite Polymorph Nanoparticles with Surface Functionalization. (1st January 2017) - Mohd Abd Ghafar, Syairah Liyana; Hussein, Mohd Zobir; Abu Bakar Zakaria, Zuki
Abstract : The development of cockle shell-based calcium carbonate aragonite polymorph nanoparticle synthesis method using the technique of mechanical stirring in the presence of dodecyl dimethyl betaine (BS-12) incorporated with surface functionalization demonstrated high homogeneity of sample product with good nanoparticles dispersion. The cockle shell-based calcium carbonate aragonite nanoparticle with functionalized surface was characterized using transmission electron microscopy (TEM), field emission scanning electron microscopy (FESEM), particle size distribution, pH measurement analysis, Fourier Transform Infrared (FTIR) spectroscopy, and X-ray diffraction (XRD). Surface functionalization was proven to improve the overall size and shape of the nanoparticles and enhance their dispersion properties, preventing coarse agglomeration among nanoparticles in general. The improved method was verified to retain its aragonite crystalline nature. Additionally, surface functionalization did not increase the size of nanoparticles throughout the modification process. This facile preparation using naturally occurring cockle shells as the main source is environmentally friendly because it provides relatively low cost of raw material source as it is abundantly available in nature and has good mineral purity content. Hence, high quality production of surface functionalized cockle shell-based calcium carbonate aragonite polymorph nanoparticles can potentially be exploited and produced on a large scale for various industrial applications, especially for biomedical purposes in the near future.